School Policies and Primary School Architecture in the City of Annaba (ex Bône), Algeria, 1830-1962 - Youbi, Maroua; Rehailia, Hassib; Taliano-Des-Garets, Françoise (African historical review, 2024)
This study investigates the history of the French colonial architecture of schools in the city of Annaba (ex Bône) in Algeria by spotlighting the buildings and their characteristics to identify the links between educational colonial policies, primary school architecture, and the context of their creation. This historical perspective enhances our understanding regarding the evolution of the architecture of Bône primary schools. Although the construction of public infrastructure at that time followed the movement of building Algerian cities to occidental standards, the issue of education and the construction of primary schools was extremely political, since French public instruction in Algeria was an integral part of the political project of colonial conquest. Primary school was a powerful tool of moral conquest; it began with a civilising mission then shifted to assimilation and integration. The evolution of the production of primary schools testifies to the seal of the various colonial educational policies, laws, and successive reforms that spread over this period, which influenced the school and its architecture.